Dominicans towards the liturgical celebration of the immaculate conception of the blessed Virgin Mary (13th –16th centuries) - Kochaniewicz, Bogusław (Bogoslovni vestnik, 2024)
The study entitled “Dominicans Towards the Liturgical Celebration of the Immaculate Conception of the Blessed Virgin Mary (13th –16th Centuries)” presents the position of the Order of Preachers towards the celebration of the Immaculate Conception. It reveals the reasons that influenced the negative attitude of Dominicans towards this truth of faith. Apart from the negative opinion of St. Thomas Aquinas on this topic, it also presents other, no less important motives that contributed to taking an irreconcilable position on the liturgical celebration of Conceptio Mariae, which have so far remained unknown. The analysis carried out allowed to discover that the unfavorable position of the Order towards the feast of the Immaculate Conception was not only the result of Dominicans identifying with the doctrine of St. Thomas Aquinas, but his motives lay much deeper and touched key aspects of the broadly understood theology and liturgy of that time.
Keywords: brezmadežno spočetje Device Marije; celebration; Dominicans; dominikanci; immaculate conception of the Blessed Virgin Mary; liturgija; liturgy; praznovanje